Antiadhesive and antibiofilm effect of malvidin-3-glucoside and malvidin-3-glucoside/neochlorogenic acid mixtures upon staphylococcus - Silva, Sara (2022)
Several reports on the biological activity of anthocyanin-rich extracts have been made. However, despite the association of said activity with their anthocyanin content, to the best of our knowledge, there are no previous works regarding the antimicrobial, antibiofilm and/or antiadhesive properties of anthocyanins alone. Therefore, the present work aimed to determine the effects of malvidin-3-glucoside, a major component of a previously reported extract, and the impact of its association with neochlorogenic acid (the only non-anthocyanin phenolic present in said extract), upon several Staphylococcus strains with varying resistance profiles. Results show that, while malvidin- 3-glucoside and malvidin-3-glucoside/neochlorogenic acid mixtures were unable to considerably inhibit bacterial growth after 24 h, they still possessed an interesting antibiofilm activity (with reductions of biofilm entrapped cells up to 2.5 log cycles, metabolic inhibition rates up to 81% and up to 51% of biomass inhibition). When considering the bacteria’s capacity to adhere to plain polystyrene surfaces, the inhibition ranges were considerably lower (21% maximum value). However, when considering polystyrene surfaces coated with plasmatic proteins this value was considerably higher (45% for adhesion in the presence of extract and 39% for adhesion after the surface was exposed to extract). Overall, the studied anthocyanins showed potential as future alternatives to traditional antimicrobials in adhesion and biofilm formation prevention.